Has the HIV epidemic in rural Mwanza, Tanzania reached a plateau? - Mwita, W; Chilongani, J; White, R; Mshana, G; Changalucha, J; Mosha, F; Ross, D; Zaba, B; Todd, J (Tanzania Journal of Health Research, 2008)
Data from studies in Mwanza Region in Tanzania suggest stabilising HIV prevalence. The objective was to determine the factors that may have contributed to the relatively stable pattern of the HIV prevalence observed in the comparison communities of the Mwanza STD treatment trial in rural Mwanza Region, Tanzania between 1991 and 2001. Socio-demographic, sexual behaviour and HIV prevalence data in two surveys conducted10 years apart in the same communities using similar sampling schemes were compared. The age standardised HIV prevalence was 3.8% (95% CI: 3.2–4.6) in 1991 and 4.3% (95% CI: 2.8–6.4) in 2001 for males (Z= - 0.56, P= 0.58); and 4.5% (95% CI: 3.8–5.3) in 1991 and 3.9% (95% CI: 2.6–5.6) in 2001 for females (Z= 0.64, P= 0.52). Participants in the 2001 survey reported significantly fewer lifetime and recent sexual partners (12 months), Sexually Transmitted disease syndromes (12 months) and significantly more condom use at last sex with casual partners than those in the 1991 behaviour survey. We conclude that STD/ HIV infection prevention activities in rural Mwanza may be responsible for changes in risky sexual behaviour and have successfully impeded the spread of HIV infection. These activities should therefore be enhanced to reduce HIV incidence even further. In addition,modelling studies are needed to assess whether mobility of HIV infected people out of rural communities may stabilise the prevalence of the HIV infection in the general populations.br> Keywords: HIV, prevalence, trend, sexual behaviour, population mobility, Tanzania Tanzania Journal of Health Research Vol. 10 (3) 2008: pp. 117-123